Deuda externa y reconocimiento. Triangulación de intereses en el conflicto México-Texas, 1837-1844 - Martínez Carmona, Gabriel (El Colegio de México, A.C., 2022)
This article is divided into three parts, organized chronologically, that address three different periods in the connection between external debt and recognition. In the first part, it analyzes the proposal to triangulate the conversion project formulated by F. de Lizardi and company in the context of the independence of Texas in the years between 1837 and 1839. The second, in turn, analyzes the formulation of the project and the experiences of the Texan emissaries to Mexico and London in search of recognition in 1839 and 1840. The third period analyzes how the idea of an indemnization payment took on a life of its own, in the sense that it was delinked from conversion and both the British and the Texan governments took on the issue as a way to incentivize the Mexican government to grant recognition, between 1841 and 1844, in which the context had changed and annexation by the United States took on greater momentum. Finally, the conclusions reflect on the relationship between external debt, indemnization and recognition.